ACHIEVEMENT OF 30 BAHT POLICY IMPLEMENTATION DURING THE YEAR 2001 TO 2011 - อร่ามวัฒนานนท์, พจน์; ดอกไธสง, บุญทัน; ทูลพานิชย์กิจ, สุดใจ; เลิศพานิช, ปิยะวรรณ (RMUTT Global Business and Economics Review, 2015)
The research on the achievement on the implementation of the 30 Baht Health Care for all sickness treatment during the year 2002-2011 has two main purposes to study the achievement of the implementation of the 30 Baht Health Care for all sickness treatment policy during the year 2002-2011 as well as to give suggestions on the improvement on factors that will have great effect on the achievement of implementation of the 30 Baht Health Care Program. This research employed both qualitative and quantitative analysis approaches, which are, by using the in-depth interview and by using questionnaires respectively. he sample group are group of managers of different level 25 persons and the group of those who receive the services in various hospital and clinics in all parts of the country, both provincial and sub-province total 300 persons, and the group of the service providers of the same locations afore mentioned total 100 persons respectively. The findings from the research are: first, the implementation of the 30 Baht health care for all sickness treatment Policy during the year 2002-2011, the research found out that both the services receivers and the services providers have their moderate satisfaction and thus the achievement of the Program is a moderate success. The second result is composed of eight topics, which are factors that have effect on the implementation of 30 Baht health care for all sickness treatment with the suggestions to improve such factors for the effectiveness in implementing the 30 Baht health care for all sickness treatment in the next phases. (1) To set up this 30 Baht health care for all sickness treatment program as the National Agenda, and must be carried on by all successive governments. All groups of people or the majority will benefit from this Project and meet the people’ basic requirement and this will give way for the effectiveness in Politics. (2) As for the control of governmental expenditures on public health care and the reduction of people’ burden on health expenditures, this will yield the effectiveness in Economics. (3) By giving people a chance of easy access to sickness treatment, and that they are covered with health insurance will also give effectiveness in Society. (4) By giving the 30 Baht health care for all sickness treatment project the same services standards as other kind of other health insurance and such services are available at all hospitals, has enough budget for it, with enough medical staffs, will also result in the effectiveness of Project Management. (5) By giving people the ability to inspect the expenditures of the project in order that the budget will be well spent, will give the effectiveness in Transparency. (6) By giving the people an easy access to the services, to have a good health with no sickness, will give the effectiveness to Community Strength. (7) Besides, to achieve the effectiveness in Satisfaction, both the services receivers and the services providers must all be satisfied with the fast and convenient deliveries of the patient. (8) With such easiness in accessing to the services at all hospitals, this will also give the effectiveness in Co-operations. All these suggestions can be used and apply in setting up the direction of implementing the Populist Policy of 30 Baht health care for all sickness treatment project in the next phase efficiently.